Site‐specific dynamics in remnant populations of Northern Wheatears Oenanthe oenanthe in the Netherlands. (19th September 2014) - van Oosten, H. Herman; Van Turnhout, Chris; Hallmann, Caspar A.; Majoor, Frank; Roodbergen, Maja; Schekkerman, Hans; Versluijs, Remco; Waasdorp, Stef; Siepel, Henk; Robinson, Rob
<x xml:space="preserve">Abstract</x> Dynamics of populations may be synchronized at large spatial scales, indicating driving forces acting beyond local scales, but may also vary locally as a result of site‐specific conditions. Conservation measures for fragmented and declining populations may need to address such local effects to avoid local extinction before measures at large spatial scales become effective. To assess differences in local population dynamics, we aimed to determine the demographic drivers controlling population trends in three remaining populations of the Northern Wheatear Oenanthe oenanthe in the Netherlands, as a basis for conservation actions. An integrated population model (IPM) was fitted to field data collected in each site in 2007–2011 to estimate fecundity, survival and immigration. Sites were 40–120 km apart, yet first‐year recruits were observed to move between some of the sites, albeit rarely. All three populations were equally sensitive to changes in fecundity and first‐year survival. One population was less sensitive to adult survival but more sensitive to immigration. A life table response experiment suggested that differences in immigration were important determinants of differences in population growth between sites. Given the importance of immigration for local dynamics along with high philopatry, resulting in low exchange between sites, creating a metapopulation structure by improving connectivity and the protection of local populations are important for the conservation of these populations. Site‐specific conservation actions will therefore be efficient and, for the short term, we propose different site‐specific conservation actions.